Improving Growth and Yield of Chilli (Capsicum spp.) Through Plant Growth Regulator Application - Siddiki, Md Habibullah; Masum, Abdullah Al; Rashid, Mamunur; Ahmed, Shah Iftekhar; Chakraborty, Bondhon (Research in Agriculture Livestock and Fisheries, 2025)
The current investigation was carried out to determine the growth and yield and Quality parameters of chilli (Capsicum spp.) as influenced by different levels of growth regulators i.e. Naphthalene Acetic Acid (NAA) and Gibberellic Acid (GA₃) There were seven treatments as follows: 1) Control (no PGR application); 2, 3, and 4) three NAA levels (30, 40, and 50 ppm), and 5, 6, and 7) three GA₃ levels (9, 10, and 11 ppm), respectively. The results reflected that the use of PGR affects plant height, number of fruits/plants, fruit length, diameter, and average weight of fruits. Among the treatments, NAA (40 ppm) (T₂) and GA₃ (10 ppm) (T₅) were recorded as significantly better than the control and other treatments. The tallest plants (50 cm) and the longest (15 cm) and widest (6 cm) fruit and highest average fruit weight (3 g) were recorded for T₂, while the greatest number of fruits per plant (30) was recorded for T₅ as well as the highest average fruit weight (4 g). Among all the parameters measured, the control (T₀) always revealed the lowest values. Significant differences among treatments were confirmed by the statistical analysis at P < 0.05. Based upon these produce characteristics, it can be recommended that application of NAA 40 ppm and GA₃ 10 ppm under field conditions can improve growth and productivity in chilli. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 253-258